Implementation of Automatic Door Hand Code at PT. Medan Sugar Industry - Hartono Hartono; Silvia Lestari; Firman Syahputra (STMIK Pontianak, 2020)
The automatic door system is a system that is used to help human performance where this system uses hand-code collected from a set of data taken by using a camera in the form of an image. Therefore the researchers conducted research for hand-code recognition in making systems, doors. automatic. use skin tone detection and overall projection to recognize human hand codes, then convert them to binary